Students need analysis in developing mobile English application for English as a foreign language young learner - Fansury, Andi Hamzah; Rahman, Ali Wira; Rampeng, Rampeng; Hamsiah, Andi (Intelektual Pustaka Media Utama, 2025)
Technology in the learning process can assist in providing teaching materials to students, making it easier for students, teachers, and parents to react whenever and wherever they are; facilitate and assist in the preparation of materials sourced from the internet; as well as assist in simulating, visualizing the learning process in a structured, processed, and scientific manner. This research analyzed the student's need to develop the mobile application. This research used the steps in the combined research and development (RD) and analysis, design, develop, implement, and evaluate (ADDIE) models. The study was conducted in Makassar, and the research subject was the students at Junior High School, with 100 randomly selected participants. The data were analyzed descriptively using interviews, observations, and participant questionnaires. The result showed that students need applications containing material that is easier to understand, using audio or video using Indonesian speakers, and interactive exercises so the students can improve their speaking skills. Based on the results of the questionnaire, the researcher synergized the school's existing curriculum with the needs analysis (N.A.) carried out by the researcher so that the results of this study would benefit the English as a foreign language (EFL) young learners, teachers, and stakeholders.